TINGKAT KERUSAKAN MINYAK KELAPA SELAMA PENGGORENGAN VAKUM BERULANG PADA PEMBUATAN RIPE BANANA CHIPS (RBC) - Herlina Herlina; Ely Astryaningsih; Wiwik Siti Windrati; Nurhayati Nurhayati (Faculty of Agricultural Technology, University of Jember, 2017)
Coconut oil is an oil produced from the old coconut that is obtained from the pulp of a coconut in the extract through the manufacture of coconut milk and finally becomes oil. The damage on oils such as oxidation reaction, hydrolysis reaction and polymerization reaction. This study aims to know the extent of coconut oil damage during repeated vacuum frying on the manufacture of Ripe Banana Chips (RBC) by testing the free fatty acids, Iodine Numbers, Peroxide Numbers, Viscosity, Specific Weight and Clarity. Fat Free Acid Content, Iodine Numbers and Peroxide Numbers are determined by iodometric method, viscosity by oswald viscometer method, specific gravity by pycnometer and clarity by spectrophotometer. The sample is coconut oil in each fryer by using a vacuum fryer. Measurement is repeated with three times for each oil. The results showed that average oil free fatty acid analysis was 0,1944% - 0,2414%. Iodine ranges from 41,783mg/g-45,7141mg/g. Peroxide numbers range from 2,5909mekO2/kg-3,067mekO2/kg. The average yield of viscosity analysis ranged from 0,0205Poise-0,0333Poise. Specific gravity ranged from 0,9144g/ml-0,9193g/ml. The average results of clarity analysis ranged from 0,0788-0,0928. The conclusion of this study is the more frequent oil that’s used with vacuum frying on the manufacture of Ripe Banana Chips (RBC) can caused the quality of oil is decreased. This is indicated by the increase of free fatty acid content, peroxide number, specific gravity, viscosity and decrease of iodine number and clarity. Keywords: oil rancidity, coconut oil, vacuum frying, ripe banana chips (RBC)